Factors Affecting to Fast Food Consumption Behavior Among Junior High School Students in Banyuwangi: Using Theory of Planned Behavior Approach Yusron Ami - Yusron Amin; Haswita Haswita (International Journal of Advanced Health Science and Technology, 2024)
Phenomenon of fast food consumption behavior experiencing among junior high school students have a negative impact in long-term. The study aims is to analyze factors affecting to fast food consumption behavior among junior high school students using theory of planned behavior approach. This study design using observational analytic with cross-sectional approach. This study conducted in junior high school (SMP X) in Banyuwangi with involving among 98 students as samples using simple random sampling technique. The instruments using self-administered questionnare derivered from theory of planned behavior. Bivariate and multivariate-test used to measure relationship two variables and the dominant factor. The result shows that attitude, subjective norm, and perceived behavioral control (PBC) effect on fast food consumption behavior among junior high school students, with subjective norm as a dominant factor followed by attitude, and PBC. Need an effect to reduce fast food consumption behavior among students through envolving the parents and peers, enhancing positive attitude as well as strengthening self-perceived behavioral control.